Groundwater Inrush Control and Parameters Optimization of Curtain Grouting Reinforcement for the Jingzhai Tunnel. (9th January 2021) - Li, Gan; Ma, Weibin; Tian, Siming; Hongbo, Zhou; Huabin, Fan; Zou, Wenhao
Abstract : Based on the systematic study on the characteristics of water and mud inrush during the excavation of Jingzhai tunnel, the mechanism of water inrush seepage transformation caused by excavation disturbance is analyzed. By means of electromagnetic geophysical prospecting, the potential water bearing area of the tunnel was analyzed. The constitutive model of rock mass and grouting parameters are considered in the numerical simulation. The law of tunnel crack initiation and expansion under different curtain grouting parameters is proposed. The characteristics of seepage water inrush caused by excavation are described. It is considered that there are three stages in the seepage characteristics of tunnel: incubation, sudden, and stable. Numerical simulation was used to analyze the crack propagation track and water inflow characteristics under the grouting thickness of 3 m, 5 m, and 7 m. When the curtain grouting thickness was 3 m, the fracture field penetrated the curtain grouting area. The dominant seepage channel is formed, which greatly increases the probability of water inrush. When the curtain thickness is 5 7 m, the expansion of the crack zone can be controlled basically, so that the fracture and water bearing rock layer cannot form a seepage channel. At last, the grouting scheme of 6 m thick grouting and 20 m advanced grouting was selected, and the water seepage was reduced by 83%.